A porous hexagonal boron nitride powder compact for the production and release of radioactive 11C. Issue 7 (July 2021) - Stegemann, S.; Ballof, J.; Cocolios, T.E.; Correia, J.-G.; Dockx, K.; Poleshchuk, O.; Ramos, J.P.; Schell, J.; Stora, T.; Vleugels, J.
Abstract: A porous pre-sintered hexagonal boron nitride powder compact was recently developed as target for the production of intense 11 C beams for Positron Emission Tomography -aided hadron therapy. In a previous study, this target has been characterized regarding its operational limitations. In this work, microstructural characterization with respect to the target's grain size, porosity and pore structure, and a dedicated fractional release study from activated targets, i.e. how much 11 C is extracted by a short heat treatment, is presented. Corresponding results include an average grain size of approximately 1.7(1) μm, total and open porosity of 40(5) and 21(7)%, respectively, which is mostly composed of pores with sizes ranging from 120 to 470 nm. From the measured release fraction the order of magnitude of carbon's diffusion coefficient D (1500 °C) = 10 −15 − 10 −14 cm 2 s −1 in porous boron nitride, and a 11 C extraction efficiency of about 10% at 1500 °C target temperature were estimated.